2017
DOI: 10.11152/mu-941
|View full text |Cite
|
Sign up to set email alerts
|

Serial transthoracic coronary Doppler shows complete reversibility of microvascular obstruction pattern at one month after reperfused acute myocardial infarction.

Abstract: “No reflow” phenomenon is a common complication with significant prognostic repercussions after reperfused acute myocardial infarction. Previous studies have shown the feasibility and prognostic significance of coronary microcirculation assessment by transthoracic Doppler of left anterior descending artery (LAD). The aim of the study was to evaluate the time course of the coronary microcirculation status after acute anterior myocardial infarction reperfused by primary angioplasty with stent on LAD. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…After an acute ischemic injury in the later phase of the MI microvascular function recovers, which is manifested by prolongation of the diastolic deceleration time in the IRA ( 6 , 11 , 12 ). This recovery of microcirculation is a consequence of the gradual recanalization of occluded small blood vessels and neoangiogenesis in the infarcted zone with an increase in the capacitance of intramyocardial circulation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an acute ischemic injury in the later phase of the MI microvascular function recovers, which is manifested by prolongation of the diastolic deceleration time in the IRA ( 6 , 11 , 12 ). This recovery of microcirculation is a consequence of the gradual recanalization of occluded small blood vessels and neoangiogenesis in the infarcted zone with an increase in the capacitance of intramyocardial circulation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that after acute ischemic injury, microvascular function gradually improves within one month with a subsequent increase of DDT of IRA ( 11 , 12 ). Importantly this improvement is translated into the reduction of infarct size ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 65 ], MVO was found in 56% of patients with STEMI and PCI by MRI. MVO was diagnosed by echocardiography in 50% of patients with STEMI and PCI [ 69 ]. It was reported that no-reflow (TIMI = 0–2) was documented in 25% of patients with STEMI and PCI [ 7 ].…”
Section: The Incidence Of Microvascular Obstruction the Mortality Rat...mentioning
confidence: 99%
“…Currently, the assessment of MVO often uses both angiography and MRI (Table 1 , Ref. [ 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]). However, in recent years, investigators increasingly favor MRI as a more accurate method of assessing MVO.…”
Section: Introductionmentioning
confidence: 99%
“…The persistent full no-reflow phenomenon (the Thrombolysis in Myocardial Infarction [TIMI] flow grade 0) can be angiographically found in approximately 5% of patients with AMI and PCI, but MVO may be more common [ 7 ] . MVO has been diagnosed by the contrast-enhanced magnetic resonance imaging (MRI) in 25% of patients with STEMI [ 9 ] , diagnosed angiographically in 29% of patients with both STEMI and PCI [ 10 ] , but detected by MRI in 56% of patients with both STEMI and PCI [ 11 ] and diagnosed with transthoracic echocardiography in 50% of patients with both STEMI and PCI [ 12 ] . MVO also can be detected by the angiographic TIMI flow grade in 25% of patients with STEMI and PCI in one study [ 13 ] but in 46% of patients with STEMI and PCI by the same method in another study [ 14 ] .…”
Section: Incidence Mortality and Prognosis Of Mvo In Patients With Amimentioning
confidence: 99%